O edukację przeciwko przemocy - Justyna Bojanowicz; Ewa Gawryś (Edukacja Ustawiczna Dorosłych)
Violence against women is a violation of their dignity, freedom, personal rights and fundamental rights – the right to life and health. However, not only many women do have no courage to oppose a perpetrator but also do not consider themselves a victim of domestic violence. They live in a difficult, traumatic situation, which they consider to be the norm. Rooted gender stereotypes limit the ability of women to stand up to the perpetrator. That is why anti-discrimination education and shaping pro-active social attitudes are important. As long as violence in a family is treated as a private matter for its members, the situation of women will not change. There cannot be any tolerance for domestic violence in society. The paper presents selected aspects from the research on the situation of women experiencing domestic violence. They draw attention to the need for broad social education strengthening the sense of sensitivity to domestic violence. Actions focused only on criminal consequences of the perpetrator will not significantly contribute to the reduction of the occurrence of acts of domestic violence.